THE IMPACT OF HINDI CINEMA ON ALTERING THE ADULTS’ PERCEPTION TOWARDS SOCIETAL STEREOTYPES: A STUDY OF DELHI NCR - Singh, Karan; Pasha, Mohammad Aamir; Rai, Shivendu Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Hindi cinema, with its immense popularity and pan-India reach has long been recognized as an influential socio-cultural force in the country. Through propagation of enduring stereotypes in films, it contributes to shaping and reinforcing the attitudes and perceptions of audiences regarding gender roles, communities, professions and societal values. This study aimed to examine the impact of exposure to stereotypical Hindi cinema on altering adults’ perceptions towards commonly accepted societal stereotypes in the Delhi NCR region. A sample of 217 adults aged 18-35 above years was surveyed using questionnaires to assess cinema viewership patterns, endorsement of societal stereotypes portrayed in Hindi movies. The findings highlight the powerful influence Hindi cinema wields in combating regressive stereotypes in society especially among vulnerable sections like the rural poor with limited education. But rising education levels are breeding resistance to such stereotyped beliefs. The paper recommends that Hindi filmmakers should consciously avoid harmful stereotypes and attempt progressive portrayals of gender, caste, class and professions. Responsible cinema can play a transformative role in promoting egalitarian attitudes aligned with India’s development goals.